The 2010 International Joint Conference on Neural Networks (IJCNN) 2010
DOI: 10.1109/ijcnn.2010.5596867
|View full text |Cite
|
Sign up to set email alerts
|

Curiosity and pleasure

Abstract: Heuristic decision making received wide attention due to the work of Tversky and Kahneman (1981) and inspired multiple studies of irrationality of the human mind and a fundamental disregard for knowledge. But what is the source of all human knowledge, including heuristics? We discuss the hypothesis that acquisition of knowledge is a deeply rooted psychological need, a motivational mechanism for perception as well as higher cognition. We report experimental results showing that acquisition of knowledge is emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 47 publications
1
41
0
1
Order By: Relevance
“…Recent experimental studies [71] confirmed existence of the knowledge instinct and aesthetic emotions related to knowledge. Using neuro-imaging studies such as [4,23,77,78] mathematical mechanisms in this paper should be related to specific mind's modules and circuits.…”
Section: Future Directionsmentioning
confidence: 86%
“…Recent experimental studies [71] confirmed existence of the knowledge instinct and aesthetic emotions related to knowledge. Using neuro-imaging studies such as [4,23,77,78] mathematical mechanisms in this paper should be related to specific mind's modules and circuits.…”
Section: Future Directionsmentioning
confidence: 86%
“…The finding that curiosity experiences were valenced in this way was unexpected, because previous definitions of curiosity have emphasized knowledge-seeking rather than knowledge-avoidance (Grossnickle, 2016). In one exception however, Perlovsky, Bonniot-Cabanac, and Cabanac (2010) asked adult men and women about their curiosity to learn information such as "Do you know the criteria used to rank restaurants?" and these authors used the term "negative curiosity" in cases when participants rejected the opportunity to learn the information.…”
Section: Aim 1: Characteristics Of the Curiosity Experiencementioning
confidence: 98%
“…Merak, zihnin çeşitli işlevleriyle ilişkili karmaşık bir eğilimidir (Perlovsky, Bonniot-Cabanac ve Cabanac, 2010). Merak; yeniliğin ve sorunun tanınması, efor sarf etme ve öz düzenlenme ile ilişkili olumlu duyuşsal-motivasyonel sistem olarak kavramsallaştırılmıştır (Kashdan, Rose ve Fincham, 2004).…”
Section: Merakunclassified